Culturally Responsive Game-Based Learning: Integrating PjBL to Enhance Students' Understanding of Linear Equations - Sasna Pratiwi; Moh. Mahfud Effendi; Siti Khoiruli Ummah; Zulkifley Mohamed (Jurnal Pendidikan Progresif, 2026)
This study aims to develop and evaluate PjBL-based educational games that integrate mathematics learning with local culture in senior high schools, specifically a game called "Uno Math Culture". This research is motivated by observations that high school students' understanding of learning is limited by conventional methods and the lack of interactive media, so it is necessary to develop PjBL-based educational games that integrate local cultural contexts to create more meaningful, contextual, and engaging mathematics learning. This study employed a Research and Development (R&D) approach based on the ADDIE model. The subjects consisted of 31 tenth-grade students. The data collection techniques used were questionnaires and tests: questionnaires were used to assess validity and practicality. In contrast, tests were used to assess the effectiveness of using educational games. The validation results from three academics and one practitioner indicated an 86.40% level, categorized as "highly valid". The results of the student response questionnaire showed a practicality of 85.32%, categorized as "very practical". In terms of effectiveness, the product significantly improved students’ learning outcomes (t(30) = -6.568, p < 0.05) with a large effect size. Overall, the development of a PjBL-based educational game, entitled “Uno Math Culture,” that integrates mathematics and local culture for 10th-grade students at SMA 1 Ponggok has proven to be valid, practical, and effective in integrating mathematics learning with the local cultural context. Keywords: educational games, local culture, mathematics learning,  PjBL.